2012
DOI: 10.3892/mmr.2012.1102
|View full text |Cite
|
Sign up to set email alerts
|

Expression of APP, BACE1, AChE and ChAT in an AD model in rats and the effect of donepezil hydrochloride treatment

Abstract: Abstract. The aim of this study was to investigate the pathological changes in a rat model of Alzheimer's disease (AD) and the effect of donepezil hydrochloride (HCl) treatment. The rat model of AD was established by the bilateral injection of amyloid β 1-40 (Aβ 1-40 ) into the hippocampus. Changes in spatial learning and memory functions were examined using the Morris water maze test and changes in catalase (CAT) and glutathione peroxidase (GSH-Px) activities were determined using chemical colorimetry. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Memory dysfunction is well known to be associated mainly with cholinergic neuron loss in several regions of the brain, especially the basal forebrain and hippocampal CA1 region [15,16,17]. Consistent with previous studies [18,19,20], ChAT (a specific marker for cholinergic cells) immunohistochemical results from this study indicated cholinergic neuron loss in the MS and hippocampal CA1 regions in AD-like mice.…”
Section: Resultssupporting
confidence: 91%
“…Memory dysfunction is well known to be associated mainly with cholinergic neuron loss in several regions of the brain, especially the basal forebrain and hippocampal CA1 region [15,16,17]. Consistent with previous studies [18,19,20], ChAT (a specific marker for cholinergic cells) immunohistochemical results from this study indicated cholinergic neuron loss in the MS and hippocampal CA1 regions in AD-like mice.…”
Section: Resultssupporting
confidence: 91%
“…Choline acetyltransferase is encoded by the ChAT gene located on chromosome 10q 11.2 (Francis et al, 1999;Li et al, 2012). The ChAT rs2177369 polymorphism plays an important role in the formation of acetylcholine.…”
Section: Chatmentioning
confidence: 99%
“…The expression of APP cleaving enzymes is increased in the brain cortex of AD patients [ 41 ] and the mRNA expression of APP was also increased in AD rat models [ 42 ], and these effects are also associated with elevated brain A β concentrations [for review, see [ 43 ]]. It has been suggested that the activities of β - and γ -secretase enzymes are enhanced in the brains of AD individuals [ 33 , 44 ], which could elevate brain A β levels leading to formation of senile plaques (A β deposit) [for review, see [ 45 ]].…”
Section: Introductionmentioning
confidence: 99%